CSR i etyka przekonań - Soin, Maciej (Annales. Etyka w Życiu Gospodarczym, 2019)
Examples of scandals related to exposing the unethical practices of companies which are classified as CSR leaders include cases where their declarations on undertaking social responsibility, as well as spending a lot of money on spectacular social campaigns and then rigorously reporting it in the appropriate documents, are accompanied by acts of abusing workers’ and environmental rights, misleading customers, i.e., abusing consumer rights, and finally “tax optimisation”, which generates measurable losses to the local communities. These cases raise the question about the reason for corporate social responsibility not being immune to abuse or opportunities to treat it as merely an image-related issue. The problem is presented using Max Weber’s widely known typology. It contrasts the ethics of conviction (ruled by the principle of intentionally keeping to the rules which have been adopted as being right) with the ethics of responsibility for the consequences of actions, including those that were undertaken in good faith but which have unintentional consequences. The usefulness of Weber’s typology when considering CSR problems becomes evident when we notice that the dominant interpretation of the corporate social responsibility concept, with its characteristic emphasis on voluntariness and positivity of actions within CSR, brings this concept closer to the ethics of conviction model. Voluntary actions in the field of CSR should go beyond carrying out regular goals of economic activities, i.e., the maximisation of profits, by providing good quality, desirable goods and services. However, what should be considered a prosocial activity –and thus, social responsibility –remains unclear in some companies. In accordance with the thesis of the paper, this ambiguity is one of the important factors that create discrepancies between declarations and real corporate activities. As we can see, the focus on voluntarily doing good which has been adopted in the current interpretation of CSR pre-empts the pursuit to avoid bad practices, both in theory and in the implementation of CSR programmes. Moreover, the CSR-dominant interpretation leads to a particular terminological confusion and replaces the companies’ responsibility towards concrete stakeholders, which is appropriate for the economic activity, with an abstractly understood responsibility towards an abstractly understood society. In this sense, the conceptual analysis of the relationship between CSR and ethics reveals that one of the important sources of problems with CSR is joining this concept with an unsuitable model of ethics. This is not because of the alleged defects of the ethics of conviction, appreciated by Weber, among other thinkers, but because it is a model that, in fact, is not suitable for business ethics. If the ethics of conviction is private, then it cannot be used to regulate social relations. In conclusion, it may be stated that, paradoxically, a dominant way of thinking about the social responsibility of corporations leads more to separation than to bringing together ethics and business. CSR, in its current form, cannot be an efficient means of implementing ethical objectives in business because it defines the issue of social responsibility as a sphere of private beliefs and arbitrary interpretations. Therefore, it undermines the relevance of the proper and socially significant notion of responsibility for economic activities and their consequences. Of course, the CSR concept can and should be modified; the question remains as to whether eliminating the elements that bring it closer to the ethics of conviction does not actually translate into giving it up entirely.